Atmospheric River Precipitation Enhanced by Climate Change: A Case Study of the Storm That Contributed to California's Oroville Dam Crisis. Issue 3 (4th March 2022) - Michaelis, Allison C.; Gershunov, Alexander; Weyant, Alexander; Fish, Meredith A.; Shulgina, Tamara; Ralph, F. Martin
Abstract: An increasingly volatile hydroclimate increases California's reliance on precipitation from atmospheric rivers (ARs) for water resources. Here, we simulate the AR that contributed to the Oroville Dam crisis in early February 2017 under global climate conditions representing preindustrial, present‐day, mid‐, and late‐21st century environments. This event consisted of two distinct AR pulses: the first snowy, westerly, and cool followed by a southwesterly and warm pulse resulting in copious rain‐on‐snow. We estimate that climate change to date results in ∼11% and ∼15% increase in precipitation over the Feather River Basin in Northern California for the first and second pulses, respectively, with late‐21st century enhancements upwards of ∼21% and ∼59%, respectively. Although both pulses were enhanced by the imposed climate changes, the thermodynamic response and subsequent precipitation increases were most substantial during the second pulse. The disparate changes demonstrated here highlight that not all ARs will respond similarly in a warmer world. Plain Language Summary: California's reliance on precipitation from atmospheric rivers is expected to increase as our climate warms. Understanding how climate change is impacting this increasingly dominant mode of precipitation is vitally important for water‐resource management throughout the state, across the North American West Coast, and for other similarly impacted regions. Our case study of an impactful atmospheric river from early February 2017 that contributed to the Oroville Dam crisis in Northern California, modeled under preindustrial, present‐day, mid‐, and late‐21st century unabatedly warming environments, demonstrates an overwhelming increase in precipitation throughout the event. This particular storm was comprised of two distinct pulses, and while both pulses of the storm are enhanced in the warmer future epochs, the estimated precipitation increases are disproportionately higher for the second pulse due to larger increases in temperature and moisture. Our results therefore suggest that not all atmospheric rivers are similarly affected by climate change and point to specific directions for relevant future research. Key Points: Climate change enhanced the precipitation associated with the February 2017 atmospheric river over Northern California The two distinct pulses comprising this event were differentially impacted A stronger thermodynamic response during the second pulse enabled a precipitation increase more than double that of the first pulse